The autophagy component LC3 regulates lymphocyte adhesion via LFA1 transport in response to outside-in signaling - Naoyuki Kondo; Yuko Mimori-Kiyosue; Keizo Tokuhiro; Giuseppe Pezzotti; Tatsuo Kinashi (Nature Communications)
Abstract The leukocyte integrin LFA1 is indispensable for immune responses, orchestrating lymphocyte trafficking and adhesion. While LFA1 activation induces LFA1 clustering at the cell contact surface via outside-in signaling, the regulatory mechanisms remain unclear. Here, we uncovered a previously hidden function of the autophagosome component LC3 beyond its role in autophagy by bridging two seemingly unrelated pathways: LFA1 transport and autophagosome transport. LFA1 clusters co-trafficked with LC3, facilitating LFA1 accumulation at the contact surface. LC3b knockout decreased lymphocyte adhesiveness. LFA1 activation did not induce autophagy, whereas it increased mTOR and AMPK activity. LFA1-dependent AMPK activation enhances LFA1 and LC3 clustering and adhesion. Inhibiting Mst1 kinase-mediated LC3 phosphorylation promoted LC3-mediated LFA1 recruitment to the contact surface through direct interaction with RAPL, uncovering an unprecedented integrin recruitment route. These findings uncover a function of LC3 and expand our understanding of lymphocyte regulation via LFA1.